2020
DOI: 10.1155/2020/3863269
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and DNA-Binding Kinetics of New Pd(II) and Pt(II) Thiosemicarbazone Complexes: Spectral, Structural, and Anticancer Evaluation

Abstract: In a bid to come up with potential anticancer agents, a class of thiosemicarbazone ligands bearing substituted thiophene were synthesized followed by complexation with various Pd(II) and Pt(II) metal precursors. The ligands (E)-1-((thiophen-2-yl)methylene)thiosemicarbazide (L1), (E)-1-((4-bromothiophen-2-yl)methylene)thiosemicarbazide (L2), and (E)-1-((5-bromothiophen-2-yl)methylene)thiosemicarbazide (L3) were synthesized by condensation reactions and obtained in good yields. Complexation of L1 and L2 with Pd(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…This comparison as given in Table 8 further indicated that compound 3 binds significantly with ds‐DNA. [ 11,49–55 ] In comparison with our previously reported work, [ 11 ] in present studies, the binding constant was evaluated 10 order of magnitude higher for compound 3 . The reason of comparatively stronger binding could be attributed to the presence of chlorine in the structure.…”
Section: Resultsmentioning
confidence: 84%
“…This comparison as given in Table 8 further indicated that compound 3 binds significantly with ds‐DNA. [ 11,49–55 ] In comparison with our previously reported work, [ 11 ] in present studies, the binding constant was evaluated 10 order of magnitude higher for compound 3 . The reason of comparatively stronger binding could be attributed to the presence of chlorine in the structure.…”
Section: Resultsmentioning
confidence: 84%
“…This decreases the probable transitions, and the effect is observed as a hypochromic shift. [ 43,44 ] To estimate the binding affinity of L 1 ‒L 3 and 1‒9 toward CT‐DNA, the intrinsic binding constant K b was calculated using the Wolfe‐Shimer equation (Equation ) by determining the ratio of the slope to the intercept from the plot of [DNA]/( ε a – ε f ) versus [DNA]. [DNA]εaεf=[DNA]εbεf+1Knormalbεbεf, $\frac{[\mathrm{DNA}]}{{\varepsilon }_{{\rm{a}}}-{\varepsilon }_{{\rm{f}}}}=\frac{[\mathrm{DNA}]}{{\varepsilon }_{{\rm{b}}}-{\varepsilon }_{{\rm{f}}}}+\frac{1}{{K}_{{\rm{b}}}}{\varepsilon }_{{\rm{b}}}-{\varepsilon }_{{\rm{f}}},$where [DNA] is the concentration of the CT‐DNA, ε a , ε b , and ε f are apparent, fully bound complex, and free complex extinction coefficients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41][42] T A B L E 3 Mean ± standard deviation values of in vitro antioxidant activities of L 1 -L shift. [43,44] To estimate the binding affinity of L 1 -L 3 and 1-9…”
Section: Anticancer Studiesmentioning
confidence: 99%
“…51 Through noncovalent interactions such as groove and intercalation modes, certain thiosemicarbazone Pd complexes exhibit weak binding to DNA. 52,53 Their cytotoxic effects are not countered by the low preference for DNA. Without preferential DNA binding, other Pd targets, such as topoisomerase I and II, which have a positive correlation with colon cancer, are highly effective at causing cell death.…”
Section: The Dna Fragmentationmentioning
confidence: 99%